Humor w walce z pandemią koronawirusa - Mielcarek , Mirosław (Studia Edukacyjne, 2021)
The aim of the article was to analyze humorous content that relates to the COVID-19 pandemic of SARS-CoV-2. The main part of the text was preceded by an analysis of the literature on the subject of the meaning of humor in human life, including coping with it in difficult situations. When proceeding to the implementation of the presented article, the slogan “# stay at home” was followed. Therefore, to achieve this goal, online resources were used. The literature on the subject was searched using the popular scientific search engine Google Scholar, while humorous content related to the coronavirus was obtained through social and information portals. The subject matter is close to its author because he himself struggled with coronavirus infection and humor no doubt helped survive the hard moments.